The effect of repetitive transcranial magnetic stimulation (rTMS) add on serotonin reuptake inhibitors in patients with panic disorder: a randomized, double blind sham controlled study - Prasko, Ján; Záleský, Richard; Bares, Martin; Horácek, Jirí; Kopecek, Milan; Novák, Tomás; Pasková, Beata (Neuro endocrinology letters, 2007)
BACKGROUND: Transcranial magnetic stimulation (rTMS) can modulate cortical activity. The goal of our study was to assess whether rTMS would facilitate effect of serotonin reuptake inhibitors in patients with panic disorder. METHOD: Fifteen patients suffering from panic disorder resistant to serotonin reuptake inhibitor (SRI) therapy were randomly assigned to either active or to sham rTMS. The aim of the study was to compare the 2 and 4 weeks efficacy of the 10 sessions 1 Hz rTMS with sham rTMS add on SRI therapy. We use 1 Hz, 30 minutes rTMS, 110% of motor threshold administered over the right dorso-lateral prefrontal cortex (DLPFC). The same time schedule was used for sham administration. Fifteen patients finished the study,. Psychopathology was assessed using the rating scales CGI, HAMA, PDSS and BAI before the treatment, immediately after the experimental treatment and 2 weeks after the experimental treatment by an independent reviewer. RESULTS: Both groups improved during the study period but the treatment effect did not differ between groups in any of the instruments. CONCLUSION: Low frequency rTMS administered over the right dorso-lateral prefrontal cortex after 10 sessions did not differ from sham rTMS add on serotonin reuptake inhibitors in patients with panic disorder.
Keywords: Prefrontal Cortex; kombinovaná terapie; Selective Serotonin Reuptake Inhibitors; Male; Combined Modality Therapy; Serotonin Uptake Inhibitors; panická porucha; transkraniální magnetická stimulace; Transcranial Magnetic Stimulation; prefrontální mozková kůra; Adult; selektivní inhibitory zpětného vychytávání serotoninu; dospělí; mužské pohlaví; Severity of Illness Index; dvojitá slepá metoda; úzkost; lidé; ženské pohlaví; Humans; antidepresiva; stupeň závažnosti nemoci; Double-Blind Method; Female; Panic Disorder; Antidepressive Agents; lidé středního věku; Anxiety; Middle Aged